CULTURAL CHANGE AND POLICY IMAGES IN POLICY SUBSYSTEMS. (8th October 2015) - ROBINSON, ROBERT R.
Abstract : Baumgartner and Jones' theory of conflict expansion highlights the importance of policy imagery in the maintenance of policy subsystems, as a sharp increase in negative imagery can drive conflict expansion and subsystem dissolution. However, we still know relatively little about what drives rapid shifts in image valence. In this study, I examine how cultural change affects receptiveness to policy images, drawing on the cultural theory (CT) developed by Douglas and Wildavsky. Affecting both perception and risk assessment, cultural commitments impact how policy images are received. Returning to the policy subsystem anchored in the Atomic Energy Commission, I find that its imagery – well suited for an earlier cultural milieu – created negative associations for egalitarians, who were increasingly prevalent during this time frame. As my study shows, CT can add to the study of administration by helping us better understand, categorize, and predict which images and institutions may be endangered by specific cultural changes.